Millennial Generation of Go-Food Transactions in The Era of New Normal - Ni Made Silvia Oktaviani; I Gede Sanica (Institute of Computer Science (IOCS), 2020)
Since the COVID-19 pandemic, the Central Government of the Republic of Indonesia has announced policies related to COVID-19 prevention to carry out all activities from home. To meet primary needs, one of which is food and drink during the COVID-19 pandemic in the era of new normal, the millennial generation prefers to use food delivery service. The problem in this research is finding an understanding of the millennial generation in using Go-Food during the COVID-19 pandemic in the era of new normal. Also, identifying the millennial generation's understanding of Go-Food can be one of the factors causing the high rate of fraud. This study used a qualitative descriptive method with triangulation (combined) data collection techniques. The research instrument is a questionnaire (google form) to find the key informants who are determined through the purposive sampling technique. Furthermore, key informants are interviewed to obtain in-depth information. The informants of this research are the millennial generation who use Go-Food in the Denpasar and Badung areas. Based on the research results, the millennial generation prefers to use Go-Food to make it easier to fulfill their needs during the COVID-19 pandemic. Uniquely, the millennial generation has chosen to study self-taught and use the internet to find out how to use Go-Food. Factors from the millennial generation's understanding of the features Go-Food that make them experience problems or fraud when shopping using Go-Food.